The Impact of AI on Teacher’s Profession: Beyond Boogeyman and Critique - Bagdonaitė, Jurgita; Duoblienė, Lilija (Social Welfare: Interdisciplinary Approach, 2026)
Aiming to ensure social well-being by investing in teachers’ attitudes toward technology, this study examines how the integration of Artificial Intelligence (AI) reconfigures teachers’ professional agency, while focusing on theoretical tensions between pedagogical innovation and governance-driven regulation. The analysis centers on the interaction between AI and the teaching profession, demonstrating how AI intensifies and reconfigures existing teaching theories and practices, rather than introducing an entirely new pedagogical paradigm. The study employs a theoretically grounded conceptual analysis, drawing on pragmatist-constructivist, post-structural (Foucauldian), and posthumanist perspectives, with the Actor-Network Theory (ANT) positioned as a relational analytical framework within the posthumanist tradition to examine human-technology entanglements in education. The analysis suggests that AI can support pedagogical experimentation and student-centered learning, but simultaneously introduces risks related to teacher autonomy, personalized learning, ethical responsibility, and new forms of surveillance and control. These dynamics reveal a central contradiction between pedagogical innovation and institutional regulation. The study concludes that a balanced approach which combines human agency with AI capabilities is essential for promoting equity, adaptability, and social well-being in education.